2021
DOI: 10.1093/ajhp/zxab329
|View full text |Cite
|
Sign up to set email alerts
|

Physical compatibility of Normosol-R with critical care medications used in patients with COVID-19 during simulated Y-site administration

Abstract: Disclaimer In an effort to expedite the publication of articles , AJHP is posting manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. Purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A total of 2961 publications via search of databases and 35 publications from additional sources were assessed, and 35 manuscripts were identified for inclusion (Figure 1). Six studies were adjudicated as high risk of bias 20-25 and excluded from further analysis, for a final inclusion of 29 studies 26-54 (Supplementary Figures 1 and 2). Full characteristics of all included studies can be found in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 2961 publications via search of databases and 35 publications from additional sources were assessed, and 35 manuscripts were identified for inclusion (Figure 1). Six studies were adjudicated as high risk of bias 20-25 and excluded from further analysis, for a final inclusion of 29 studies 26-54 (Supplementary Figures 1 and 2). Full characteristics of all included studies can be found in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the medications included in this review have only one unique assessment evaluated, which significantly limits generalizability. 46,48,50 Other medications were assessed in multiple different combinations but by only one study, which again limits external validity. 33,39,48 Recently the importance of utilizing balanced crystalloids instead of normal saline for resuscitation in critically ill patients has been emphasized to decrease the risk of hyperchloremic AKI, metabolic acidosis, and potentially mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations